Stereotactic Radiosurgery for Intracranial Tumors: Puerto Rico Experience - Lozada, David; Brau, Ricardo H. (Puerto Rico Health Sciences Journal, 2010)
Historically, the treatment for most intracranial pathologies has included medical management, surgery, radiotherapy and recently, stereotactic radiosurgery. Since its introduction, stereotactic radiosurgery has evolved from an investigational concept into a recognized neurosurgical procedure for the management of a wide variety of brain disorders. The goal of this research was to describe the experience in Puerto Rico using this technology and review the efficacy, safety, and role of radiosurgery in the treatment of the most common intracranial tumors treated today. Patients treated from 1999-2009 at Clínicas Las Américas were reviewed and medical literature databases were searched for articles pertaining to stereotactic radiosurgery performed in these intracranial tumor pathologies: meningiomas, gliomas, cerebral metastasis, vestibular schwannomas and pituitary adenomas. Each study was examined to determine the radiosurgical parameters, duration of follow-up review, tumor growth control rate and complications. A total of 50 peer-reviewed studies were examined. Radiosurgery in benign tumors resulted in the control of tumor size in 90% of treated patients. Unfortunately radiosurgery for malignant tumors is not curative, but has been effective in improving survival and quality of life. Although microsurgery remains the primary treatment modality in most cases, stereotactic radiosurgery offers both safe and effective treatment for much intracranial pathologies. Further refinements in the radiosurgical technique will likely lead to improved outcomes and make it a standard of care.